ANTI BREAST CANCER ACTIVITY OF ETHYL ACETATE EXTRACT OF FERMENTATION BROTH EMPLOYING ENDOPHYTIC FUNGI TAXUS SUMATRANA ISOLATES - A.T. Karossi; A Poniah; L.Z. Udin; S Rieny (Jurnal Kimia Terapan Indonesia, 2009)
Fermentation broths of TSC 18 and TSC 22 fungi isolates obtained from Taxus sumatrana plant were investigated for their in vitro anti breast cancer activity against T47D cell line. The isolates were further identified by PCR and sequencing methods. In the fermentation experiments, the growth curves were constructed by plate count method and the pH change were recorded, while glucose and protein dynamics of the broth were determined by Nelson-Somogy and Lowry methods respectively. Anti-cancer activity was assessed by SRB (Sulforhodamine B)method. The investigation indicates the fermentation broth both isolates possessed the anticancer activity with lese of 42.6 ppm for TSC 18 and 55.7 ppm for TSC 22. Cisplatin which is used as a reference compound gave ICso of 15.9 ppm . The PCR and tree view program proved that TSC 18 is Phomopsis sp. strain MAFF-238472 and TSC 22 is Coprinopsis cinerrea strain NBRC30628.Keyword: Anticance, Isolates TSC 18 and TSC 22 Taxus Sumatrana.